2023
DOI: 10.1038/s41467-023-37259-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory mechanisms of TARP γ8-selective AMPA receptor therapeutics

Abstract: AMPA glutamate receptors (AMPARs) mediate excitatory neurotransmission throughout the brain. Their signalling is uniquely diversified by brain region-specific auxiliary subunits, providing an opportunity for the development of selective therapeutics. AMPARs associated with TARP γ8 are enriched in the hippocampus, and are targets of emerging anti-epileptic drugs. To understand their therapeutic activity, we determined cryo-EM structures of the GluA1/2-γ8 receptor associated with three potent, chemically diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
(133 reference statements)
1
3
0
Order By: Relevance
“…Previously determined structures of TARPs are overall like our structure of TARPg2 (Fig. 2b), and the loop anchor DSB is within structures of TARPg3 18 and TARPg8 11,12,19 , and even previously published structures of TARPg2 6 . However, it is absent, as expected, in the structure of the type-II TARP, TARPg5 20,21 (Fig.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Previously determined structures of TARPs are overall like our structure of TARPg2 (Fig. 2b), and the loop anchor DSB is within structures of TARPg3 18 and TARPg8 11,12,19 , and even previously published structures of TARPg2 6 . However, it is absent, as expected, in the structure of the type-II TARP, TARPg5 20,21 (Fig.…”
supporting
confidence: 82%
“…2c). In contrast, the TARP cleat motif is conserved in all TARPg3, g5, and g8 subunit structures as well as GSG1L 11,18,20 (Fig. 2d).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TARPs have been shown to modulate the trafficking and gating properties of AMPARs ( Milstein and Nicoll, 2008 ). Recent findings have shown that injecting TARP γ8 ligand JNJ-61432059 into mouse BLA or ventral hippocampus could reduce and enhance GluA1- and GluA2-containing AMPARs, respectively ( Zhang et al, 2023 ), and reduce repetitive alcohol self-administration, in an animal model of addiction ( Hoffman et al, 2021 ) (for review, see ( Brogi et al, 2019 )). Taken together, these AMPAR-modulating reagents could be promising therapeutics for restoring normal social functioning in brain diseases.…”
Section: Discussionmentioning
confidence: 99%